Optimizing aerosolization of a high-dose L-arginine powder for pulmonary delivery - Satu Lakio; David A.V. Morton; Anna P. Ralph; Pete Lambert (Elsevier, 2015)
In this study a carrier-free dry powder inhalation (DPI) containing L-arginine (ARG) was developed. As such, it is proposed that ARG could be used for adjunctive treatment of cystic fibrosis and/or tuberculosis. Various processing methods were used to manufacture high-dose formulation batches consisting various amounts of ARG and excipients. The formulations were evaluated using several analytical methods to assess suitability for further investigation. Several batches had enhanced in vitro aerolization properties. Significant future challenges include the highly hygroscopic nature of unformulated ARG powder and identifying the scale of dose of ARG required to achieve the response in lungs.